‘Becoming a Reflective Educator?’: An Analysis of the Individual Career Trajectory and the Importance of Reflection for Islamic Educators - Nurwanto, Nurwanto (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
This article covers scaffolding efforts done by the writer to be a reflective educator in the middle of educational condition which is often stopped, routine and less innovative. By depending on the stages of carrier of being educator, some important inventions can be showed that between the first stage of carrier and the stage toward maturity in educating, it can be found a time of carrier transmission making ones be wary and alien to the carrier chosen. This stage must be passed by some actions not only having self reflection but also learn and adopt critically toward the best innovation and model done by other colleges. Moreover, some creativities and innovations also need to be developed, so the carrier of being an educator becomes the important choice in one’s life. This article also explains that a skill of reflection and improving the quality of work is an Islamic action for every Moslem which is having educational profession.